2022
DOI: 10.1002/dmrr.3589
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the pathogenesis of type 2 diabetes as revealed by signature genomic classifiers in an African American population in the Washington, DC area

Abstract: Aims: African Americans (AA) in the United States have a high risk of type 2 diabetes mellitus (T2DM) and suffer from disparities in the prevalence, mortality, and comorbidities of the disease compared to other Americans. The present study aimed to shed light on the molecular mechanisms of disease pathogenesis of T2DM among AA in the Washington, DC region. Methods:We performed TaqMan Low Density Arrays (TLDA) on 24 genes of interest that belong to three categories: metabolic disease and disorders, cancer-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…As there are survival differences between commercial pigs and local pigs, we have identified genes that may be related to adaptability, such as APBA1 . Previous research has linked APBA1 to cognitive function, and its absence has been associated with the onset of neurobehavioral disorders [ 39 , 40 ]. This could indicate that Chinese indigenous pigs are more intelligent and better suited to adapting to their environment.…”
Section: Discussionmentioning
confidence: 99%
“…As there are survival differences between commercial pigs and local pigs, we have identified genes that may be related to adaptability, such as APBA1 . Previous research has linked APBA1 to cognitive function, and its absence has been associated with the onset of neurobehavioral disorders [ 39 , 40 ]. This could indicate that Chinese indigenous pigs are more intelligent and better suited to adapting to their environment.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of microarray technology, the transcriptome of peripheral whole blood can be readily profiled accurately and reproducibly. Due to the richness of gene expression information, the whole blood transcriptome is an attractive field of biomarker studies for various diseases, such as infectious diseases, neurodegenerative diseases, diabetes, and cancers [15][16][17][23][24][25][26][27]. The primary objective of our study was to use a less invasive way to conduct sample collection ('liquid biopsy') to investigate the biological processes, signaling pathways, and key differentially expressed genes associated with MASLD in an understudied AA population in the US.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, whole blood is an incredibly useful tissue sample that requires minimal risk during collection (minimally invasive) and can be accurately profiled due to its richness in gene expression information. [12,13]. In our previous study, we successfully identified signature genes associated with Type 2 diabetes and related comorbidities in an US African American (AA) population by analyzing peripheral blood samples [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13]. In our previous study, we successfully identified signature genes associated with Type 2 diabetes and related comorbidities in an US African American (AA) population by analyzing peripheral blood samples [12][13][14][15][16]. The present study aims to investigate the expression levels of genes involved in Amyloid Processing using peripheral blood tissue samples from Pakistani patients with AD.…”
Section: Introductionmentioning
confidence: 99%